STIM and Orai1 Variants in Store-Operated Calcium Entry - Rosado, Juan A. (Front Pharmacol, 2016)
Store-operated Ca(2+) entry (SOCE) is an ubiquitous mechanism for Ca(2+) entry in eukaryotic cells. This route for Ca(2+) influx is regulated by the filling state of the intracellular Ca(2+) stores communicated to the plasma membrane channels by the proteins of the Stromal Interaction Molecule (STIM) family, STIM1, and STIM2. Store-dependent, STIM1-modulated, channels include the Ca(2+) release-activated Ca(2+) channels, comprised of subunits of Orai proteins, as well as the store-operated Ca(2+) (SOC) channels, involving Orai1, and members of the canonical transient receptor potential family of proteins. Recent studies have revealed the expression of splice variants of STIM1, STIM2, and Orai1 in different cell types. While certain variants are ubiquitously expressed, others, such as STIM1L, show a more restricted expression. The splice variants for STIM and Orai1 proteins exhibit significant functional differences and reveal that alternative splicing enhance the functional diversity of STIM1, STIM2, and Orai1 genes to modulate the dynamics of Ca(2+) signals.